Enhancing the students’ English skills through English Islamic tagged-media - Sulasih Nurhayati; Widya Nirmalawati (JSSH (Jurnal Sains Sosial dan Humaniora), 2021)
This paper aimed to explain a practical programme utilised to enhance the students' English skills by designing English Islamic-tagged-media. It was relatively considerable due to low proficiency, low exposures, and psychological problems the students have, which undermine the ability. Therefore, the programme was concerned with the more straightforward and uncomplicated direction the students may perform for better English proficiency. The programme involved 23 students of high schools who reside in the two Muhammadiyah orphanages of Purwokerto residence. It principally conceptualised and integrated the English skills and the religious mission of Islamic values to produce the disciples of Islam and Muhammadiyah. Furthermore, the programme used a workshop method to intensively train and guide the students to design the English tag-lines that express the Islamic values on T-shirts' media. As a result, despite the difficulties in creating the expressions and printing the T-shirts, the programme has successfully run with the excellent performance the students made. They have shown their ideas and creativities in doing some exposures to their English skills and their Islamic knowledgeability